Baseline type 2 biomarker levels and clinical remission predictors in children with asthma - Chen, Mengmeng; Li, Congcong; Yang, Qiuyan; Zhang, Huijie; Zhang, Yanli; Wang, Na; Dong, Jingcheng (Frontiers in Immunology, 2025)
BackgroundFew studies have investigated the relationship between baseline type 2 biomarker levels and clinical features in pediatric asthma, particularly in different asthma stages, which may inform prognosis and remission.ObjectiveTo explore the association between baseline Th2 biomarker levels and clinical manifestations in pediatric asthma, identifying predictors of clinical remission.MethodsThe study included 172 children with a mean age of 6.87 ± 3.04 years, comprising 119 asthma patients and 53 non-respiratory symptom controls. Clinical evaluations such as lung function tests, FeNO, total IgE, blood eosinophil counts, and skin tests were conducted. Serum biomarkers (TSLP, IL-4/5/13, TARC, Periostin), and IgE were measured by ELISA. Th2-high asthma (IgE >100 IU/mL and eosinophils≥140 cells/μL, n=110) was stratified into acute attack (n=48), persistent asthma (n=26), and clinical remission (n=36). Additionally, mouse models across asthma stages were established to measure TSLP levels in BALF, serum, and lung tissue, to validate its predictor value.ResultSerum TSLP was significantly elevated in acute exacerbation and persistent asthma(P<0.01). Multivariable regression confirmed its independent association with remission (OR=1.009, P=0.023). ROC analysis indicated moderate discriminative capacity of TSLP for remission (AUC=0.59, sensitivity=39.1%, specificity=59.4%). Murine models also showed TSLP levels normalization during remission.ConclusionSerum TSLP is independently associated with clinical remission in Th2-high pediatric asthma, though its standalone predictive accuracy is moderate (AUC=0.59). Integration with lung function and IgE may form a composite biomarker panel for remission evaluation. This stratification tool may guide asthma risk stratification and personalized disease management. Longitudinal studies are warranted to validate its prognostic utility.